Soybean spermidine concentration: Genetic and environmental variation of a potential ‘anti-aging’ constituent - Sagara, Tatsuya; Fiechter, Gregor; Pachner, Martin; Mayer, Helmut K.; Vollmann, Johann (Journal of food composition and analysis, 2017)
[Display omitted] •Soybean seed contains between 167 and 291mgkg−1 spermidine.•Spermidine concentration is influenced by soybean genotype and growing season.•Soybean seed protein content is not correlated to spermidine concentration.•Selection of soybean genotype might influence spermidine level of soy foods and their health value. Soybean seed is one of the richest food sources of spermidine and other polyamines. Recent findings from human and animal models have confirmed spermidine as a potential anti-aging substance acting through the initiation of autophagy pathways as well as through antioxidant and anti-inflammatory properties. As this might be of relevance for selecting soybeans for soy food production, the present research addresses the natural variation of spermidine concentration of soybean to determine the influences of genotype and environmental factors on spermidine and other polyamines, and to study possible relationships between spermidine and major seed quality traits. Sixteen early maturity soybean genotypes were grown near Vienna, Austria for three seasons, and harvest samples were subject to ultra-high performance liquid chromatography (UHPLC) for determining concentrations of polyamines and free amino acids. Based on individual samples, spermidine concentration ranged between 167 and 291mgkg−1 dry seed, and both genotype and growing season significantly affected spermidine level. Spermidine concentration was closely correlated to putrescine but was not related to seed protein content or other major seed constituents determined by NIRS analysis. These results demonstrate the feasibility of plant breeding approaches to modify the spermidine level of soybean which might support the future development of functional soy foods.